Evaluasi Tingkat Kematangan Tata Kelola Teknologi Informasi pada Layanan Informasi Publik dan Pengaduan Masyarakat Pemerintah Kota Kupang menggunakan COBIT 4.0 - Yohanes Payong (Jurnal Inovasi Kebijakan, 2020)
The development of Information Technology (IT) has a very significant impact on changes in the current government system. IT implementation in all sectors of government is one solution to improve the interaction of government services to the community (Government to Citizen G to C). For this reason, it is deemed necessary to apply a framework in information technology governance to ensure the application of information technology can be made possible in the government system, maximize all existing benefits, and minimize various risks to IT management properly and appropriately, in addition, it can be used as a resource by government officials responsibly. In order to achieve these objectives, it is necessary to evaluate the planning, implementation process, monitoring actions and continuous evaluation. With the implementation of Smart City, it is necessary to have a continuous evaluation of information technology services at the Kupang City Government. In this study, COBIT 4.0 is used as an IT governance approach to determine the maturity level of IT governance. This study uses six tributes of COBIT 4.0 maturity, using descriptive analysis; each maturity attribute will be evaluated to determine the maturity level of public information services and public complaint services. The results of the evaluation of this study determine two types of conditions, namely: current (as is) and expected (to be). Based on the maturity index of public information services and public complaints, the maturity index in its current state (as is) has a value of 2.0. This index value states that the predicate for maturity is "repeatable but intuitive (repetition)". This predicate shows that the information technology management process has been running and developed based on situational conditions. OPD Kupang City already has a pattern in implementing the information technology management process based on various repeated experiences that have been applied to various activities related to information technology in the past. Information technology governance procedures and processes have not been standardized, in which the responsibility is only left to certain individuals or personalities. Procedures are not formally communicated and still limited to discourse, wherein limited human resources can lead to deviations. Planning and training human resources activities are also not done formally. Meanwhile, for the maturity index of public information services and public complaints, the expected/desired condition (to be) has an index value of 5.0, wherein this index value states that the predicate of maturity is 'optimized'. The predicate of the maturity index shows high hopes for all OPDs for optimal information technology governance in public information services and public complaint services in the future. OPD's desire for this predicate hopes that there will be compatibility between various best practices that occur in other locations or OPDs outside Kupang City so that it can be further developed in each OPD, but still coordinate with the Kupang City Information and Communication Office as the leading sector. Policies related to public information service media and information system-based complaint service media must be implemented in an integrated manner to automate the workflow (computerized) online.